EXPRESSION PATTERNS OF PHOSPHATE TRANSPORTER GENE ECGPT ASSOCIATED WITH THE SALT STRESS RESPONSE IN PERENNIAL EUCALYPT TREE HYBRID CLONES - Eny Faridah (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2013)
Salinity effects on plant can often be related to mineral ion content alteration, including phosphate. Under saline conditions, phosphate levels were reported to decrease in plants. Such effects could indirectly affect intracellular phosphate levels, leading to phosphate deficiency, which in turn leads to increased activities of phosphate uptake mechanisms. This research was aimed to investigate the effects of salinity on the expression changes of phosphate transporter genes isolated from E. camaldulensis x E. globulus hybrid clones subjected to salt concentrations of 0 (control), 50, 100, and 150 mMNaCl. Fragments of genes (1164bp long and encodes 304 amino acid polypeptides) known to be involved in phosphate uptake were identified and isolated by RACE from these hybrids, encoding a Phosphate Transporter (Ecg PT). Expression studies using Northern-Blot analysis revealed that the expression of EcgPT was found to be affected by salt, suggesting a direct effect of salinity on phosphate uptake. EcgPT was expressed differently in different clones, indicating different degrees of phosphate transporter activation in order to tolerate salt stress. Molecular data are discussed in relation to measurements of ion levels in different organs of different clones and under various salt regimes during the course of the hydroponic experiment.